Everyday experiences of post-diagnosis life with dementia: A co-produced photography study. (August 2021) - Dooley, Jemima; Webb, Joe; James, Roy; Davis, Harry; Read, Sandy
There has been surprisingly little research capturing people's everyday lives in the early years following a diagnosis of dementia. This project was co-produced by three people with dementia and two university researchers. The co-researchers with dementia formulated the aims of this project as: (1) to explore post-diagnosis life with dementia and (2) to use data collection methods as a form of peer support and confidence building for the participants. The intent was to provide the opportunity to learn new skills and support participants to share their experiences without putting them on the spot. Five participants with recent diagnoses received a photography lesson and cameras to take photographs of their everyday lives. This was followed with a focus group in which the photographs were discussed. The participants used their photographs to explain: (1) the differences between their past and present with dementia, (2) how dementia affected their thought processes, (3) pets and grandchildren as facilitators of reciprocal joy and support, (4) the emotional effects of living with a dementia diagnosis, and (5) the solace and stability of nature in a changing world. The participants' creative use of photography supported them to express the complex emotions felt after a diagnosis of dementia and they reported the benefit of doing this in an environment with peers going through the same experiences. The role of the co-researchers with dementia was the key to the success of this project, drawing on their own experiences to design the project and support the participants. Future research should draw on the experiences of people with dementia to design research projects and care interventions.